Region-specific expression of a K+ channel gene in brain. - Rudy, B (1992)
Northern blot analysis and in situ hybridization studies reveal the highly localized expression in rat brain of transcripts from a gene (KShIIIA) encoding components for voltage-gated K+ channels. KShIIIA expression is particularly prominent throughout the dorsal thalamus. The expression of KShIIIA is compared to that of a closely related gene, here called NGK2-KV4. These two genes encode transcripts that induce currents in Xenopus oocytes that are as of yet indistinguishable, but they show very different patterns of expression in rat brain. NGK2-KV4 transcripts are particularly abundant in the cerebellar cortex, where KShIIIA expression is very weak. These results demonstrate the existence of cell-type-specific K+ channel components and suggest that one reason for the unusually large diversity of K+ channel proteins is the presence of subtypes that participate in specific brain functions.